1976
DOI: 10.4039/ent108127-2
|View full text |Cite
|
Sign up to set email alerts
|

A REVIEW OF THE SPIDER GENUSPHILODROMUSIN THE AMERICAS (ARANEIDA: PHILODROMIDAE)

Abstract: Philodromus Walckenaer 1826 and its seven component species groups in the Americas are defined and diagnosed. The 12 species of the aureolus group are keyed, diagnosed, and mapped. P. obscurus Blackwail, 1871 is placed in synonymy under P. cespitum (Walckenaer, 1802). P. lutulentus Gertsch, 1934 is raised to species status from synonymy under P. laticeps Keyserling, 1880, and P. eremus Buckle, 1973 is placed in synonymy under P. lutulentus. P. agreutes Schick, 1965 is placed in synonymy under P. californicus K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Later Logunov (1996) adopted this term for the ducts of the glandular heads, which may be independent of the intromittent orifice (Jäger 2002;Muster and Thaler 2003). Other related terms are 'copulatory tubes' (Dondale and Redner 1976; and previous papers), 'copulatory ducts' (Foelix 1982;Muster and Thaler 2004;Muster et al 2007), 'intromittent canal' (Ono 1988), 'insemination duct' (Szita and Logunov 2008). In my opinion, the confusion is caused by the fact that the insemination duct and the duct from the glandular heads can be incorporated in a single canal in some taxa, but they can be independent in others.…”
Section: Phylogenetic Relationships Within Philodromidaementioning
confidence: 99%
See 2 more Smart Citations
“…Later Logunov (1996) adopted this term for the ducts of the glandular heads, which may be independent of the intromittent orifice (Jäger 2002;Muster and Thaler 2003). Other related terms are 'copulatory tubes' (Dondale and Redner 1976; and previous papers), 'copulatory ducts' (Foelix 1982;Muster and Thaler 2004;Muster et al 2007), 'intromittent canal' (Ono 1988), 'insemination duct' (Szita and Logunov 2008). In my opinion, the confusion is caused by the fact that the insemination duct and the duct from the glandular heads can be incorporated in a single canal in some taxa, but they can be independent in others.…”
Section: Phylogenetic Relationships Within Philodromidaementioning
confidence: 99%
“…Simon (1932) used tibial spination as a character for intrageneric classification in Philodromus. Most subsequent authors regarded leg spination as highly variable and of little value for the clarification of relationships within Philodromidae; for example, Dondale and Redner (1976) pay little attention to spination patterns in their review of American Philodromus species-groups. The current study revealed that, despite frequent variation in individual characters, leg spination patterns as a whole are highly characteristic for superspecific taxa within the Philodromidae and often the most reliable character for the classification of species with highly derived genitalia in the system.…”
Section: Phylogenetic Relationships Within Philodromidaementioning
confidence: 99%
See 1 more Smart Citation
“…Regional Distribution: ME (Procter 1946); NH, MA, CT, NY, ON, QC, NB, NS (Dondale and Redner 1976a).…”
Section: Method: Search (1 Male 1 Female)mentioning
confidence: 99%
“…Regional Distribution: ME (Dondale 1961, as Philodromus cespiticolis Walckenaer); NH, VT, MA, NY, ON, QC, NB, NS (Dondale and Redner 1976a).…”
Section: Months: June (2 Females); July (1 Female)mentioning
confidence: 99%